Rod‐Like Sb2MoO6: Structure Evolution and Sodium Storage for Sodium‐Ion Batteries. Issue 5 (8th February 2019) - Yang, Li; Liao, Hanxiao; Tian, Ye; Hong, Wanwan; Cai, Peng; Liu, Cheng; Yang, Yingchang; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Bimetallic oxides of different metal species and well‐defined nanostructure could lead to a new generation of polymetallic oxide in the energy storage field. Exceptional 1D nanostructured materials are favorable in the electronic transmission of the kinetic processes and confinement effects of electronic structures deriving from the nanoscale dimensions. In this work, an Sb2 MoO6 nanorod is successfully prepared for the first time through a facile metathesis reaction process. Then, a thin polyaniline (PANI) layer is coated via the in situ oxidative polymerization of aniline. The Sb2 MoO6 ‐based nanorods are first utilized as anode material for sodium‐ion batteries (SIBs). Benefiting from the synergistic effect of PANI coating and 1D nanostructure, the Sb2 MoO6 @PANI nanorod electrode presents enhanced sodium storage performances, and a reversible specific capacity of 370.2 mAh g −1 can be retained after 100 cycles. Ex situ electrochemical impedance spectra (EIS) and transmission electron microscopy (TEM) are used to study the evolution process, demonstrating that the PANI coating can alleviate the pulverization of the rod structure and reflect better cycle stability. This work reveals the sodium storage activity of novel Sb2 MoO6 nanorods and proposes an efficient strategy to promote its electrochemical properties; it is in great favor of extending the development of anode materials for SIBs. Abstract : Synthesized Sb2 MoO6 nanorods are encapsulated into polyaniline through in situ oxidative polymerization of aniline. The Sb2 MoO6 @PANI nanorods are first utilized as anode material for sodium‐ion batteries and present excellent sodium storage performance, and a reversible specific capacity of 370.2 mAh g −1 can be retained after 100 cycles, which is much better than that of bare Sb2 MoO6 nanorods.